Role of attendance in academic performance of male and female medical students in pre clinical years: A descriptive study - Mohsin Ali Cheema; Amra Rehman; Saba Khalid; Syed Muhammad Hammad Ali; Rida Ajmal Khan (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: In-person attendance at medical school is a growing concern since the inception of readily available online resources. In Pakistan, a student who fails to keep up with what has been taught in class often finds academic assessments in jeopardy. The present study aimed to assess the role of attendance in academic performance among preclinical male and female students in the subject of Physiology. METHODOLOGY: Overall attendance in lectures, tutorials, and practical classes was recorded from first and second-year MBBS students’ records during the academic session of 2016-17. Scores in all written, viva voce and formative assessments were used to represent the academic performance. Data were analyzed by SPSS version 23.0. Shapiro-Wilk’s statistics were used to determine distributions. The median interquartile range (IQR) was used for non-normally distributed variables. A p-value of ≤ 0.05 was considered statistically significant. RESULTS: A total of 287 preclinical students were included in the study. Out of them, 110 (38.3%) were male, and 177 (61.7%) were females. Girls had higher overall attendance, 91% (87.2-95) as compared to the boys, 88.9% (85.6-93.2) of both MBBS years (p = 0.015). Girls also had a significantly higher percentage of scores in all formative assessments in tutorials, 65.7% (59.2-73.9) as compared to the boys, 59.6% (53.1-66.4) (p < 0.001). A positive correlation of all academic performance parameters was observed with the overall attendance (p < 0.001). The same correlations were also seen among the groups based on gender as well as the MBBS year. CONCLUSION: Attendance at medical school, especially in the subject of Physiology, is related to better academic performance. Female students are more regular and have the habit of attending classes which reflects on their better performance in formative assessments. A satisfactory overall attendance observed in our study might be due to the mandatory attendance policy of our medical school.